2020
DOI: 10.1016/j.joule.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Local CO2 Concentration as a General Strategy for Enhancing C−C Coupling in CO2 Electroreduction

Abstract: Local environment plays an important role in steering the reaction pathways in electrochemical CO 2 reduction reaction. Here, we present three approaches to modulate local CO 2 concentration in gas-diffusion electrode flow electrolyzers. Employing monodisperse Cu 2 O nanoparticles as the model catalysts, we demonstrate that providing a moderate local CO 2 concentration is effective in promoting C-C coupling. Ultimately, this study serves as a rational guide to tune CO 2 mass transport in gas-diffusion electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
256
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(287 citation statements)
references
References 46 publications
4
256
0
Order By: Relevance
“…A comparison of their CO 2 RR performance was shown in Supplementary Fig. 15d : the partial current density and total Faradaic efficiency for CO 2 RR on the Cu/C-extra electrode was similar to that of the Cu/C electrode, but the Faradaic efficiency for C 2+ products was lower on the Cu/C-extra electrode, which was attributed to the relatively lower concentration of CO 2 inside the catalyst layer 16 . This is reasonable as CO 2 needs to diffuse over a longer distance on average to reach the catalyst particles in a thicker catalyst layer.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A comparison of their CO 2 RR performance was shown in Supplementary Fig. 15d : the partial current density and total Faradaic efficiency for CO 2 RR on the Cu/C-extra electrode was similar to that of the Cu/C electrode, but the Faradaic efficiency for C 2+ products was lower on the Cu/C-extra electrode, which was attributed to the relatively lower concentration of CO 2 inside the catalyst layer 16 . This is reasonable as CO 2 needs to diffuse over a longer distance on average to reach the catalyst particles in a thicker catalyst layer.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, the electrochemical reduction of CO 2 over Cu-based catalysts has received considerable interest, because Cu exhibits appreciable activity for C–C coupling to form multicarbon products, including ethylene, ethanol, and propanol 13 , 14 . While efforts are focused on developing catalytic materials, it is also critical to understand other factors beyond catalytic materials, such as the local environment of the catalysts 15 , which can mediate the transport and local concentration of reaction species and influence reaction pathways 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It indicates there is still an ample space to explore in the aspect of the reaction device and system, such as electrolyte, membrane engineering, and counterreactions. [140] For example, the recent development of solid electrolyte membrane, such as solid alkaline polymer electrolytes, has benefited the anion exchange membrane (AEM) fuel cells with high peak power and good stability, which can be the reference for ECO 2 RR. [141] The mechanic strength, ionic conductivity, and the alkaline stability still need further improvement for better performance of AEM devices.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, it has been demonstrated that C 2+ selectivity could be enhanced by tuning CO 2 mass transport via the catalyst layer structure, feed concentration, and flow rate of CO 2 in gas-diffusion electrode electrolyzers. Modulation of local CO 2 concentration enabled an optimized faradaic efficiency toward C 2+ products of up to 75.5% at 300 mA cm −2 in 1.0 M KHCO 3 [86].…”
Section: Introductionmentioning
confidence: 99%